House dust mites stimulate thymic stromal lymphopoietin production in human bronchial epithelial cells and promote airway remodeling through activation of PAR2 and ERK signaling pathway - Yi-An Hsieh; Yi-Han Hsiao; Hsin-Kuo Ko; Yi-Luen Shen; Chien-Wen Huang; Diahn-Warng Perng; Kang-Cheng Su (Scientific Reports)
Abstract House dust mites (HDM) are common aeroallergens linked to airway inflammation and remodeling in asthma. Protease-activated receptor 2 (PAR2) and thymic stromal lymphopoietin (TSLP) may mediate these immune responses. However, how the epithelium influences fibroblasts toward airway remodeling remains unclear. We hypothesize that HDM stimulates human bronchial epithelial cells (HBECs) to produce TSLP via PAR2 activation, driving fibroblasts toward remodeling processes. HBECs were treated with HDM, with or without the PAR2 antagonist FSLLRY-NH2 (FSL), and TSLP expression was measured by qPCR and ELISA. Phosphorylation of MAPKs was assessed by western blotting. Human lung fibroblasts (HLFs) were exposed to recombinant TSLP or conditioned medium (CM) from HDM-stimulated HBECs, with or without anti-TSLP antibodies. Fibroblast proliferation and collagen production were assessed as remodeling markers. HDM increased ERK phosphorylation (not p38 or JNK) and TSLP expression at mRNA and protein levels. FSL preincubation significantly reduced ERK phosphorylation and TSLP production: HDM-stimulated CM induced fibroblast proliferation and collagen production, effects suppressed by anti-TSLP or FSL. Direct treatment with recombinant TSLP also promoted fibroblast proliferation and collagen synthesis. These findings suggest that HDM promotes HBEC-to-HLF paracrine interactions via PAR2-ERK-TSLP axis, participating in airway remodeling. PAR2 antagonists may represent potential therapeutic targets for HDM-induced remodeling processes.